Relationship Between Dietary Variety and Frailty in Older Japanese Women During the Period of Restriction on Outings Due to COVID-19. (2nd December 2020) - Otaki, Naoto; Yano, Megumu; Yokoro, Miyuki; Tanino, Norikazu; Fukuo, Keisuke
Abstract: Objectives: To investigate the relationship between diet and frailty in community-dwelling older adults during the period of restriction on outings due to novel coronavirus disease 2019 (COVID-19). Method: A mail survey targeting adults aged 65 years or older, including questions on sex, age, height, weight, and social participation, was conducted in May 2020. The participants' dietary variety score and frailty score were then calculated. Results: Overall, 322 women aged 65 years or older and who were living in the community were recruited for the study; 253 were finally analyzed. The mean age of the 253 participants was 80.0 ± 6.4 years. The dietary variety score and frailty scores were significantly correlated in the linear regression analysis (β: −0.224, p < .001). In the multivariate regression analysis, these factors remained significantly correlated in Model 1, which was adjusted for age (β: −0.229, p < .001), and Model 2, which was adjusted for age, body mass index, and other confounding factors (β: −0.208, p = .001). Discussion: Diet was correlated with frailty in older adults living in the community during the period of restriction on outings due to COVID-19.